Microencapsulated chañar phenolics: A potential ingredient for functional foods development - Costamagna, Milena Soledad (2017)
In this work, a Geoffroea decorticans (chañar) extract very rich in polyphenols and with antioxidant and inhibitory activity against pro-inflammatory enzymes, was microencapsulated in a zein matrix using electrospraying to improve its stability and facilitate its handling as food ingredient. The electrosprayed microcapsules were characterized in terms of morphology, encapsulation efficiency, water sorption ability and release properties at different pH and during an in vitro digestion process. The bioactivity of the encapsulated extract in terms of inhibitory activity on enzymes related to the metabolic syndrome were also evaluated and compared to that of the non-encapsulated ingredient. Results showed that microencapsulation did not affect biological activity and effectively protected the bioactive polyphenols during the simulated digestion process. Therefore, this encapsulation structures could be considered a potential ingredient for functional food development.